2000
DOI: 10.1159/000018502
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Pemphigoid Associated with Silicosis

Abstract: Bullous pemphigoid (BP) has never before been reported to associate with silicosis, although there are numerous reports of silicosis accompanied by different autoimmune diseases, such as systemic sclerosis, systemic lupus erythematosus, dermatomyositis or rheumatoid arthritis. We report on a 63-year-old Japanese patient with silicosis who developed tensed bullae, erosions and macular pigmentation on the trunk and extremities. Indirect immunofluorescence revealed anti-basement-membrane-zone antibodies; immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…In addition, we detected anti-topoisomerase I Ueki et al 2001aUeki et al ,b, 2002, anti-desmoglein (Ueki et al 2000(Ueki et al , 2001a, anti-caspase 8 , and anti-CD95/Fas (Takata- Tomokuni et al 2005) antibodies. Particularly for the detection of anti-caspase 8 antibody and anti-topoisomerase I antibody, the HLA (Human Leukocyte Antigen) types of proteins found in the SIL were investigated.…”
Section: Various Autoantibodies and Alteration Of The Cd95/fas Moleculementioning
confidence: 77%
“…In addition, we detected anti-topoisomerase I Ueki et al 2001aUeki et al ,b, 2002, anti-desmoglein (Ueki et al 2000(Ueki et al , 2001a, anti-caspase 8 , and anti-CD95/Fas (Takata- Tomokuni et al 2005) antibodies. Particularly for the detection of anti-caspase 8 antibody and anti-topoisomerase I antibody, the HLA (Human Leukocyte Antigen) types of proteins found in the SIL were investigated.…”
Section: Various Autoantibodies and Alteration Of The Cd95/fas Moleculementioning
confidence: 77%
“…Also, we did not include in this analysis certain other even less common autoimmune diseases also associated with silica, for example, ANCA-associated vasculitis, Sjögren syndrome, "overlap" syndromes, and even pemphigus. 10,11,[25][26][27][28] There are other study limitations that should also be noted as well. The job exposure matrix subcategory of other inorganic dusts captures a heterogeneous group of exposures.…”
mentioning
confidence: 99%
“…In previous papers [5, 6, 7], we reported that pemphigus vulgaris, pemphigus foliaceus and bullous pemphigoid were associated with long-term silicosis. Silicosis is well known to be a causative factor in several autoimmune diseases and collagen diseases [8, 9, 10, 11, 12, 13]and pemphigus may also be one of these autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports [5, 6, 7], we described 2 cases of pemphigus and 1 case of bullous pemphigoid associated with silicosis. As it is well known, some silicosis patients suffer from concomitant autoimmune diseases or collagen diseases, such as systemic sclerosis [8, 9], systemic lupus erythematosus [10, 11], rheumatoid arthritis [12], dermatomyositis [13]or Sjögren syndrome [13].…”
Section: Introductionmentioning
confidence: 99%